Notícia em tempo real : as implicações da instantaneidade na legitimidade e na credibilidade telejornalísticas - Scirea, Bruna Weis (2016)
Under the vast area of Applied Social Sciences, in the sphere of Communication and Journalism Studies, this research discuss the television broadcast journalism in the beginning of 21st century. This study starts with the hypothesis that the evolution of internet communication has a direct impact over all the communication processes, which include television, likewise television journalism, one of the most well-established formats. This impact is the rise of the instantaneousness in the news spread processes, resulting in the increase of live broadcasting. The general purpose is to analyse the consequences that the temporality modification in news broadcasting, wich became more immediate due to the progress and the convergence of new technologies, has in the legitimacy and in the credibility of the television broadcast performance. This research took as subject the coverage of Paris simultaneous attacks, on November 13th 2015, performed by ―Globo News‖, a brazilian news television channel. Ninety-one samples of the television broadcast coverage were used. These samples were released on the channel website in the first five days of the coverage and were studied using the techniques of Content Analysis, according to Bardin´s (1977) perspective. The theoretical ground is based on, among others, Becker (2005), Rezende (2000), Emerim and Cavenaghi (2012), Fechine (2008), Franciscato (2003), Silva (2008), Vizeu (2008).